Antiphospholipid syndrome in renal transplantation. Issue 4 (April 2014) - Barbour, Thomas D; Crosthwaite, Amy; Chow, Kevin; Finlay, Moira J; Better, Nathan; Hughes, Peter D; Cohney, Solomon J
Abstract Antiphospholipid syndrome (APS) may occur in isolation or in association with systemic lupus erythematosus (SLE), with the potential to cause renal failure via several distinct pathologies. Renal transplantation in the presence of APS carries a risk of early graft loss from arterial or venous thrombosis, or thrombotic microangiopathy (TMA). Whilst perioperative anticoagulation reduces the risk of large vessel thrombosis, it may result in significant haemorrhage, and its efficacy in preventing post‐transplant TMA is uncertain. Here, we report a patient with end‐stage kidney disease (ESKD) due to lupus nephritis and APS, in whom allograft TMA developed soon after transplantation despite partial anticoagulation. TMA resolved with plasma exchange‐based therapy albeit with some irreversible graft damage and renal impairment. We discuss the differential diagnosis of post‐transplant TMA, and current treatment options.